Gross hematuria and congestive heart failure – two sides of the same coin - Carmen Vasile; Daniela Pacurar; Ioana Oprescu; Raluca Vlad (Romanian Journal of Pediatrics, 2024)
Poststreptococcal glomerulonephritis (PSGN) is an immune-mediated disease following infection with nephritogenic strains of group A β-hemolytic Streptococcus (GAS), affecting children aged of 2 to 10. We report 2 different presentations of PSGN from “Grigore Alexandrescu” Hospital. Case 1: A 5 years old girl was admitted for gross hematuria. Investigations revealed: anemia, inflammatory syndrome, mild nitrogen retention syndrome, elevated ASO and low levels of serum C3, nephritic-range proteinuria and severe hematuria. she received antibiotic treatment with initial improvement. A relapse occurred in one week, a second course of antibiotic and corticosteroids was necessary. Case 2: A 15-year-old girl was admitted for acute cardiac failure, hypertension and oliguria. Investigations revealed anemia, nitrogen retention, dyslipidemia, inflammatory syndrome, high ASO titers, low serum C3, microscopic hematuria, nephrotic-range proteinuria. She had fluid build-up in both lungs and pericardium. The diagnosis was PSGN and congestive heart failure (volume overload). She received antibiotics, diuretics and ACE inhibitors. PSGN is re-emerging in pediatric practice due to the resurgence of streptococcal infections within children's communities. The clinical presentation might be highly variable, ranging from hematuria to heart failure. Clinicians should be aware and actively consider this diagnosis.